The Management of Amniotic Fluid Embolism from the ICU Perspective - Mingwang Jia; Jialin Yang; Biying Luo; Yihuan Lai; Ying Yang; Yichun Wang (IMR Press, 2024)
Objective: This review provides a comprehensive intensive care unit (ICU) perspective on amniotic fluid embolism (AFE), encompassing its epidemiology, pathophysiology, diagnosis, and management. Mechanism: AFE is an abrupt and perilous condition. The enhancement of diagnostic criteria, starting from the understanding of pathologic physiology, can facilitate the development of more specialized disease management approaches and targeted interventions. Findings in Brief: Significant research advancements have improved the timeliness and accuracy of clinical diagnosis and treatment for AFE, leading to the development of several effective rescue procedures. Progress is expected to be made in various aspects including a comprehensive exploration of pathophysiological mechanisms, identification and utilization of biomarkers, innovation in treatment methods, enhancement of personnel training and collaboration within treatment teams, as well as the application of big data technology. Conclusions: The recent research has greatly contributed to substantial progress in the clinical diagnosis and treatment for AFE. However, further research holds potential to provide even greater benefits for patients.